Why teaching? Perspectives from first-year South African pre-service teachers - Moeniera Moosa (Perspectives in Education, 2020)
South African initial teacher education institutes are currently experiencing an annual increase in admissions of first-year students. In addition, the increasing attrition rate of newly qualified teachers is of concern globally. This begs the question of why students are opting for teaching as a profession.  This study focuses on reasons why first-year students have opted to study teaching at a South African University. The theoretical lens used is linked to the expectancy-value theory of achievement motivation (Wigfield & Eccles, 2000). Five hundred and eighty first year students participated in a mixed methods research study. Data was analysed by using theories of career motivation categories namely altruistic, extrinsic and intrinsic reasons. The findings indicate that more than half (60%) of the participants were motivated to do teaching for altruistic reasons, followed by almost a quarter (23%) choosing teaching for extrinsic reasons and lastly 17% opting to become teachers for intrinsic reason. This paper argues that it would be prudent for initial teacher education institutes to understand students’ rationale for selected teaching to support them to complete their qualification and remain in the profession.